BERPIKIR ANALOGIS DALAM MENYELESAIKAN MASALAH MATEMATIKA - admin, admin; Zawawi, Irawani (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2017)
The analogy has been widely used in real life. Analogies are often used in mathematical problem solving. Therefore, every student must learn how to use the analogy in problem solving. Especially when he was bench school, the analogy is often used to solve problems that are similar to each other or the source of the problem and the target problem. Thinking analogy in mathematical problems solving, with the following phases: 1) Encoding, which identifies existing information on the source of the problem and the problem of the target; 2) Inferring, that concludes to use concepts, formulas or definitions in resolving resource issues; 3) Mapping, ie patterns or how to resolve the problem source is mapped to resolve the target problem; 4) Applying, namely completing the target problem.